Techincal Planning Of Strategical Bridge in Way Umpu Way Kanan Regency - Aditya, I Gede Putu Indra; Diana, I Wayan; Sebayang, Surya (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2020)
The Way Umpu Bridge is located in Blambangan Umpu District, Way Kanan Regency which ispart of the Trans-Central Sumatra road section. In the structural elements of the bridge damageoccurs in the structural elements on the bridge so that it can endanger road and bridge users.Therefore effective and efficient planning is needed for the design of the new bridge.Standards used as a reference in planning the Way Umpu Bridge are SNI 1725-2016, RSNI T-02-2005 and PUPR PERMEN NUMBER 28 / PRT / M / 2016. By using supporting software for thecalculation and design of AutoCAD 2017, Microsoft Excel 2013, Google Earth Pro and SAP 2000V 14.The results of this plan are (1) effective type of bridge top structure is a class A bridge framestructure with a span length of 60 m, (2) the type of effective lower structure used is a supportedT-type support and the foundation of the pre-cast concrete piles ( rotating) pile), and (3) totalconstruction costs provided by labor costs, supply of materials and equipment, heavy equipmentoperating and rental costs and taxes of Rp 16,644,725,377.